A 4, 300‐year History of Dietary Changes in a Bat Roost Determined From a Tropical Guano Deposit. Issue 4 (6th April 2021) - Gallant, L. R.; Fenton, M. B.; Grooms, C.; Bogdanowicz, W.; Stewart, R. S.; Clare, E. L.; Smol, J. P.; Blais, J. M.
Abstract: Bats provide numerous ecosystem services as they pollinate, disperse seeds, and reduce insect populations. It is thus vital to monitor and understand their foraging habits. We analyzed sterols and stanols in a rare discovery of a ∼4, 300‐year‐old bat guano deposit from a Jamaican cave to infer relative changes in bat feeding guilds over four millennia. In this deposit, zoosterols and phytosterols, in conjunction with δ 13 C and C/N data, revealed two periods of increased frugivory relative to insectivory from ca. 1000‐500 BCE and ca. 700–1900 CE. We propose two possible explanations for these intervals of increased frugivory relative to insectivory. (1) Previous paleoclimate data suggested these intervals were warmer and drier in the region, which we hypothesize resulted in reduced insect availability. We supported these inferences by comparing the same analytes in fresh guano from frugivorous, insectivorous, and sanguinivorous (blood‐drinking) bats, which showed that bats with animal‐based diets produced guano with lower C/N ratios and higher cholesterol/(cholesterol + sitosterol) ratios than those with fruit‐based diets. (2) The change in the chemical composition of the bat guano during these two periods may also be the result of a shift in the relative species composition of the bat roost that is a greater proportion of frugivorous relative to insectivorous bats during these two periods. This novel, non‐invasive method, based on the chemical composition of bat guano, tracked changes in tropical bat foraging habits extending back in time over four millennia. Plain Language Summary: Bats play important roles in pollinating flowers, dispersing seeds, and controlling insect populations. It is therefore important that we understand how human activities and natural events alter bat feeding habits, which can affect their ability to perform these important functions. Our study consisted of two parts. First, we showed how the chemical composition of fresh bat guano revealed whether bats ate plants, insects, or blood. We then used this information to study a ∼4, 300‐year‐old bat guano core collected from a cave in Jamaica to determine if we could observe long‐term dietary changes in the bat roost. Our study revealed alternating periods of increased fruit relative to insect consumption. We suggest that (1) the bat roost generally favoured a fruit‐based diet during warmer and drier periods, suggesting that climate affected feeding habits; and/or (2) the roost was composed of more frugivorous relative to insectivorous bats during those two periods. This relatively non‐invasive method offers a new way to study how bat feeding guilds are affected by different environmental conditions and will be useful to monitor and protect bat populations in the future. Key Points: Bat foraging habits can be studied by analyzing their guano for sterols, stanols, and stable isotopes of carbon and nitrogen The diets of frugivorous, nectarivorous, and sanguinivorous bats were well‐characterized by the sterol and stanol ratios in their guano We examined the composition of a 4, 300‐year‐old bat guano deposit and identified two periods of increased fruit‐based foraging